2006
DOI: 10.1002/glia.20463
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic neuroepithelial and radial glial cells generated from six human embryonic stem cell lines in serum‐free suspension and adherent cultures

Abstract: The great potential of human embryonic stem (hES) cells offers the opportunity both for studying basic developmental processes in vitro as well as for drug screening, modeling diseases, or future cell therapy. Defining protocols for the generation of human neural progenies represents a most important prerequisite. Here, we have used six hES cell lines to evaluate defined conditions for neural differentiation in suspension and adherent culture systems. Our protocol does not require fetal serum, feeder cells, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
132
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 87 publications
11
132
1
Order By: Relevance
“…Three experimental protocols that were previously shown to induce differentiation of hESCs into predominantly neuronal cells, oligodendrocytes and astrocytes were employed. [41][42][43] In all three protocols, PrP C expression was suppressed starting from day zero and the suppression was continued until the experimental end-point, day 40.…”
Section: Silencing Of Prpmentioning
confidence: 99%
See 1 more Smart Citation
“…Three experimental protocols that were previously shown to induce differentiation of hESCs into predominantly neuronal cells, oligodendrocytes and astrocytes were employed. [41][42][43] In all three protocols, PrP C expression was suppressed starting from day zero and the suppression was continued until the experimental end-point, day 40.…”
Section: Silencing Of Prpmentioning
confidence: 99%
“…43 Briefly, after culturing in feeder free conditions, hESC colonies were incubated in neural induction medium (NIM, DMEM:Neurobasal (1:1) supplemented with 1x N2 and 1x B27 supplements and 2mM Glutamax) for one day. Then, hESCs were cultured on non-adherent culture dishes in NIM until they form uniformed aggregates for 2-4 d. Floating aggregates were transferred to neural proliferation medium (NPM, DMEM:Neurobasal (1:1) supplemented with 0.5x N2 and 0.5x B27 supplements, 2mM Glutamax and 20 ng/ml FGF2) on day 5.…”
Section: Induced Differentiation Of Hescsmentioning
confidence: 99%
“…In contrast, it was suggested that neuroepithelial formation may be a default process during neural differentiation of ESCs in vitro (Liour et al, 2006). Nat et al, (2007) have also shown that the addition of RA is not mandatory for the induction of neuroepithelial phenotype. Further, RA in concert with bFGF signaling leads to the differentiation of spinal motor neurons (Mizuseki et al, 2003, Wichterle et al, 2002.…”
Section: G B C D E F H I J Kmentioning
confidence: 99%
“…Hence they can be expanded to large numbers [Phillips et al, 2008] and be differentiated into most cells of the human body, including the CNS. These properties make them an ideal resource for highthroughput cell-based assayology, including a potentially unlimited supply of neural derivatives [Nat et al, 2007].…”
Section: Human Embryonic Stem Cellsmentioning
confidence: 99%